Improved of Multiobjective Fuzzy Probabilistic Solid Transportation Models in Transportation Systems - Susanti, Eka; Dwipurwani, Oki; Dewi, Novi Rustiana; Prahesti, Wanodya Eka; Safira, Indri Yune (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2024)
Transportation activities are stages in the product distribution system. The purpose of the transport system is to minimize the total cost. If there is more than one objective function and consider more than one type of vehicle, it is called a multiobjective solid transportation problem. In some cases, the parameter transportation model is under uncertainty. A probabilistic and fuzzy approach can be used. This research introduces a probabilistic fuzzy multiobjective solid transportation model where the source, destination and vehicle parameters follow the Pareto distribution. A triangular fuzzy number expresses the coefficient of the objective function. The obtained model is applied to the problem of the metal crate transportation system. There are two objective functions; the first is the objective function to minimize the total cost. The second is the objective function to minimize the total transportation time. Three types of vehicles are considered: HDL, Engkel and Wingbox. The result is that the total cost is Rp. 3836595, and the total time is 757.245 minutes or 13 hours.